Nutrient contents and rumen degradation characteristics of grass hay in kars district - İsmail Kaya; Ahmet Öncüer; Sedat Yıldız (Eurasian Journal of Veterinary Sciences)
In this study, dry matter (DM), ash, crude protein (CP), crude fiber (CF), ether extract (EE), neutral detergent fibre (NDF) content of hay samples collected from 5 different regions of Kars distnct (Kars, Susuz. Arpaçay, Akyaka, Diğor) were determined. Their degradability characteristics and effective degradabilities were assessed for DM. OM, CP and CF by incubation in the rumen for 4, 8, 16. 24 and 48 h. Average DM. ash, CP. CF, EE and NDF in the hay samples were 90 49. 8.82, 10.56, 34.07, 2.24 and 65,28 %, respectively Rumen degradabilities of DM, OM, CP and CF were 71.50, 71.64, 76.55, 63.96 %, respectively for 48 h. and their effective degradabilities were 62.40, 62.06, 67,78, 52.94 % (k=0.02/ h) respectively. In conclusion, in terms ol their nutritional values and degradability characteristics in the rumen, hay samples produced in Kars district were in medium quality.